PERILAKU CARING PERAWAT DI RUANG RAWAT INAP DI RUMAH SAKIT SUAKA INSAN BANJARMASIN 2020 - Chrisnawati Chrisnawati; Maria Cardoso Lima; Bernadeta Trihandini; Anastasia Maratning (Journal of Nursing Invention, 2020)
Background: In the era globalization, the demands of society for adequate health services are more increasing and spurring hospitals to provide the best services so that they are not marginalized by the community. Caring as the basis and center of nursing practice. The benefits of caring are very important in the provision of nursing services based on the caring of behavior of nurses able to improve the quality of health services. Transpersonal caring recognizes unity in life and relationships that have concentric caring circles from individuals, to other, to society, to the world, to the earth and to the universe. Objective: To describe behavior caring nurses in the inpatient care in Suaka Insan Hospital Banjarmasin 2020. Method: This research uses descriptive quantitative method. The samples of this study are 95 respondent. The instrument used questionnaire and univariate analyzed with distribution frequention. Technique sampling with Purposive sampling. Result: The result of study are (1) characteristic respondent according to gender majority are female (52,6 %), (2) characteristic according to age majority are 31-50 years old (41 %), (3) characteristic according to base education majority are based SMA (49,4 %), (4) characteristic according to the respectful deference is good (62%), (5) characteristic according to the assurance of human presence is good (62%), (6) characteristic according to the positive connectedness is good (79%), (7) characteristic according to the professional knowledge and skill is good (85%), (8) characteristic according to the attentive to others experience is good ( 94 %), (9) base on the overall category is good (71 %). Conclusion: Description of the behavior caring of nurse in the inpatient room care in Suaka Insan Hospital Banjarmasin 2020 is good (71 %), and nurses are expected to maintain and improve of caring behavior. Upgrade of based nursing service, nurse caring behaviors be obtained improve the quality of health services.